Patient-Reported Outcomes Following Medial Patellofemoral Reconstruction With Peroneus Longus Allografts Demonstrate Good Results - Joseph Long, M.D; Nicholas Pappa, B.S; Michael Stitgen, M.D; David C. Flanigan, M.D; Brian Fowler, B.S; Alex C. DiBartola, M.D; Robert A. Magnussen, M.D., M.P.H (Elsevier, 2023)
Purpose: To evaluate the recurrent dislocation risk and patient-reported outcomes of peroneus longus allograft tissue for medial patellofemoral ligament (MPFL) reconstruction. Methods: Patients who underwent MPFL reconstruction with peroneus longus allograft at an academic center between 2008 and 2016 were identified. Record review and patient contact were used to identify any cases of recurrent patellar dislocation and collect patient-reported outcomes scores (Knee injury and Osteoarthritis Outcome Score [KOOS], Norwich Patellar Instability score, Marx activity scale). Patients with 1-year minimum follow-up were included. Outcomes were quantified and the proportion of patients reaching a previously defined patient acceptable symptom state (PASS) for patellar instability was determined. Results: Sixty-one patients (42 female and 19 male) underwent MPFL reconstruction with peroneus longus allograft during the study period. Forty-six patients (76%) with 1-year minimum follow up were contacted at a mean of 3.5 years postoperative. The mean age at time of surgery was 22 ± 7.2 years. Patient-reported outcomes data were available in 34 patients. Mean KOOS subscale scores were as follows: Symptoms 83.2 ± 19.1, Pain 85.2 ± 17.6, Activities of Daily Living 89.9 ± 14.8, Sports 75 ± 26.2, and Quality of Life 72.6 ± 25.7. The mean Norwich Patellar Instability score was 14.9% ± 17.4%. The mean Marx activity score was 6.0 ± 5.2. No recurrent dislocations were noted during the study period. Sixty-three percent of patients who underwent isolated MPFL reconstruction met PASS thresholds in at least 4 of 5 KOOS subscales. Conclusions: The use of a peroneus longus allograft in MPFL reconstruction in conjunction with other indicated procedures results in a low re-dislocation risk and a high proportion of patients meeting PASS criteria for patient-reported outcome scores 3 to 4 years postoperatively. Level of Evidence: IV, case series.